Evaluation of a bounded high order upwind scheme for 3D incompressible free surface flow computations - Ferreira, V. G.; Kurokawa, F. A.; Oishi, C. M.; Kaibara, M. K. [UNESP]; Castelo, A.; Cuminato, J. A. (Elsevier B.V., 2009)
fit the context of normalized variable formulation (NVF) of Leonard and total variation diminishing (TVD) constraints of Harten. this paper presents an extension of it previous work by the authors for solving unsteady incompressible flow problems. The main contributions of the paper are threefold. First, it presents the results of the development and implementation of a bounded high order upwind adaptative QUICKEST scheme in the 3D robust code (Freeflow), for the numerical solution of the full incompressible Navier-Stokes equations. Second, it reports numerical simulation results for 1D hock tube problem, 2D impinging jet and 2D/3D broken clam flows. Furthermore, these results are compared with existing analytical and experimental data. and third, it presents the application of the numerical method for solving 3D free surface flow problems. (C) 2007 IMACS. Published by Elsevier B.V. All rights reserved,
Keywords: High order bounded upwind; Free surface flow; Navier-Stokes equations; Convection terms; Finite difference method